THE SPECIFICITY OF THE SEMANTIC ORIENTATIONS OF STUDENTS CHOOSING THE PROFESSION OF A TEACHER (Conferencea, 2022)
The purpose of this article was to identify the specifics of the meaning of life orientations of people choosing the profession of a teacher, and to describe its change with age. It is shown that teacher students significantly differ from medical students and economists in all parameters of the test of meaningful life orientations, demonstrating the highest values. There are no such differences among specialists. With an increase in work experience, the importance of the life process parameter increases for economists, and for teachers, the values ​​on the scales of life control and control - I decrease.